The Effect of Guided Virtual Perineal Exercises on the Incidence and Severity of Birth Canal Tearing in Normal Vaginal Delivery - Hafidz, Aflahul; Fadholi, Ibrahim (Trigin Institute, 2025)
Perineal tearing is a common complication of normal vaginal delivery and is associated with short- and long-term maternal morbidity, including pain, infection, dyspareunia, and pelvic floor dysfunction. Although perineal exercises are recommended to reduce perineal trauma, their effectiveness in routine practice is often limited by inadequate guidance and low adherence. This study aimed to examine the effect of guided virtual perineal exercises on the incidence and severity of birth canal tearing in normal vaginal delivery. A quasi-experimental study with a control group was conducted among pregnant women in the third trimester (28-36 weeks of gestation). Participants were allocated to an intervention group receiving guided virtual perineal exercises or a control group receiving standard antenatal care. The intervention consisted of structured pelvic floor and perineal stretching exercises delivered through a virtual platform using recorded instructional modules and periodic live guidance by trained healthcare professionals. The primary outcome was the incidence and degree of perineal tearing, classified using standardized clinical criteria. Data were analyzed using descriptive statistics, bivariate tests, and multivariate logistic regression to control for confounding variables, including parity, maternal age, neonatal birth weight, episiotomy use, and duration of labor. The incidence of perineal tearing was lower in the intervention group compared to the control group. Participants who followed the guided virtual perineal exercise program experienced predominantly no or mild perineal tears, while moderate tears were more frequent in the control group. After adjustment for confounding factors, guided virtual perineal exercises remained significantly associated with a reduced risk of perineal tearing. Improved adherence to perineal exercises was observed among women in the intervention group. Guided virtual perineal exercises are an effective, safe, and non-invasive antenatal intervention for reducing the incidence and severity of birth canal tearing in normal vaginal delivery. The findings support the integration of virtual perineal exercise programs into routine maternal health services to enhance antenatal education, improve maternal comfort, and promote better childbirth outcomes.